2009
DOI: 10.1097/nen.0b013e3181a7c14e
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Activation in Axons and Schwann Cells in Experimental Sciatic Nerve Injury and Its Role in Modulating Axon Regeneration: Studies With Etanercept

Abstract: Early inflammatory events may inhibit functional recovery after injury in both the peripheral and central nervous systems. We investigated the role of the inflammatory tumor necrosis factor/nuclear factor-kappaB (NF-kappaB) axis on events subsequent to sciatic nerve crush injury in adult rats. Electrophoretic mobility shift assays revealed that within 6 hours after crush, NF-kappaB DNA-binding activity increased significantly in a 1-cm section around the crush site. By immunofluorescence staining, there was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
(42 reference statements)
1
30
0
Order By: Relevance
“…Evaluation of immunostaining. Immunoreactivity (IR) scores were assigned as described previously (Ravizza et al, 2006;Iyer et al, 2010) by a blinded investigator. Assigned scores represent averages for all cells in the sciatic motor neuron pool.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of immunostaining. Immunoreactivity (IR) scores were assigned as described previously (Ravizza et al, 2006;Iyer et al, 2010) by a blinded investigator. Assigned scores represent averages for all cells in the sciatic motor neuron pool.…”
Section: Methodsmentioning
confidence: 99%
“…Neuronal overexpression at high levels of wild-type (WT) or mutant TDP-43 in transgenic mice caused a dose-dependent degeneration of cortical and spinal motor neurons but with no cytoplasmic TDP-43 aggregates (Wegorzewska et al, 2009;Stallings et al, 2010;Wils et al, 2010;Xu et al, 2010), raising the possibility that an upregulation of TDP-43 in the nucleus rather than TDP-43 cytoplasmic aggregates may contribute to neurodegeneration. In fact, TDP-43 has been reported to be upregulated in the CSF of patients with ALS (Kasai et al, 2009) and in peripheral blood lymphocytes from ALS patients (Mougeot et al, 2011;Nardo et al, 2011). Recently, we reported that TDP-43 is upregulated in the spinal cord of sporadic ALS cases at both the mRNA and protein levels (Swarup et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through TNFR1, NF-κB is activated by TNF-α, leading to a pro-inflammatory process. NF-κB is a key modulator of Wallerian degeneration for successful axon regeneration (Smith et al, 2009). …”
Section: Gdf-15 and Axon Myelination/remyelinationmentioning
confidence: 99%
“…To investigate whether there was a difference between WT and KO animals in terms of demyelination and regeneration, representative genes were studied, including Krox-20 for demyelination , NF-κB for activation of glial cells (Nickols et al, 2003;Smith et al, 2009), MAC-2 for macrophage-Schwann cell interaction (Saada et al, 1996;Stoll and Muller, 1999) and NCAM for SC migration (Hansen et al, 2008;Thomaidou et al, 2001). After SN crush, the distal Segments C from WT and KO animals were collected at different time points, RNAs and proteins were isolated for qRT-PCR and Western blot analysis.…”
Section: Demyelination and Regeneration Related Genes In Wt And Gdf-1mentioning
confidence: 99%